Los problemas familiares dentro del contexto escolar, en los estudiantes de los quintos grados de la unidad educativa mixta Educare fundación CISOL, periodo lectivo 2013 – 2014 - Buele Ochoa, Walter Fabian (2015)
In the world, especially in Latin America, most marriages occur daily family problems that lead to divorce and separation, causing a large number of students present a low academic performance and attitudes inappropriate in school as a result of I observe daily in their homes. 2014, which raised overall objective to improve performance - FAMILY PROBLEMS IN THE SCHOOL CONTEXT IN STUDENTS OF THE FIFTH DEGREE OF EDUCATIONAL MIXED UNIT "EDUCARE" FOUNDATION CISOL, semester 2013: In this context an investigation was carried out academic students with family problems; for compliance methodology was used methods: scientific, inductive, deductive, analytic-synthetic, and statistics; that allowed several general criteria relate to formulate the problem; also facilitated sort, group or systematize information collected through the use of field instruments for tabulation thereof; the techniques used in the research development were the interview applied by the interview guide to teaching; The survey, conducted through a questionnaire to the Parent; and, the test applied by a questionnaire to students; for which population was taken as 30 students, 30 parents and one teacher, so check the issues raised. From which we can conclude that in the families of some students of the fifth grade, parents always quarrel or fight in front of their children, since students are notorious for not feel motivated to do their homework, so his grades are low, to implement this training workshops for parents can improve their performance in correspondence to set a better example and education in values; relative to completed by parents is recommended, maintaining an adequate behavior towards preventing children fight or argue; the (I) basic general education teachers, concerned to correct the behavior of their students giving personal talks to students with low grades to determine the causes and find ways to help them improve; and finally to the authorities and teachers of schools of basic education, make and use educational workshops on the importance of avoiding family problems to ensure the good performance of students in school.